Klippel-Trenaunay Syndrome of the Rectosigmoid Colon Presenting as Severe Anemia - Tetangco, Eula Plana (ACG Case Rep J, 2016)
A 23-year-old female with Klippel-Trenaunay syndrome presented with abdominal pain and severe anemia. Colonoscopy revealed diffuse venous congestion extending circumferentially from the midsigmoid to the rectum, with multiple large varicosities. This case emphasizes that Klippel-Trenaunay syndrome may have visceral manifestations beyond the classic presentation, which can be a significant source of morbidity and mortality.